Perancangan Antarmuka Sistem Informasi Manajemen Kelurahan dengan Menggunakan Metode Human-Centered Design (Studi Kasus: Kantor Kelurahan Penanggungan Kecamatan Klojen Kota Malang) - Hilda Khairunnisa; Satrio Hadi Wijoyo; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Penanggungan Village Office is an office that conducts management related to public services and population services located in Malang, especially in the District of Klojen. Based on the research results, there are several problems in the office related to management in archiving, reporting on data for monthly or annual data, management on citizen certificates, and no history of citizen letters. These problems make the staff in charge feel difficult in finding information and data, so the need for interface design by using a prototype to adjust user needs in the appearance of the Village management information system to expedite the performance of its services and expedite the work process. The desired interface is adjusted first to the needs of users using the help of Human-Centered Design (HCD) methods that aim as a focused approach to the user in the design. The evaluation applied was Heuristic Evaluation (HE) which aims to review the findings of problems on the prototype. The next evaluation is an interview to the user to validate the results of the prototype to do the display improvement process. Evaluations that have been carried out produced 16 problems. The results of this study are able to determine the design process and provide information on the results of the evaluation of the prototype design that has been made.